Environmental Impact Assessment in the Indian Ocean: Ambiguities and opportunities under the UN High Seas Treaty 2023 - Perera, L.A.R.R. (University of Colombo, 2024)
In June 2023, the international community adopted the historic High Seas Treaty, extending legal protection to oceans beyond national jurisdictions with a focus on the conservation and sustainable utilisation of the high seas. This Treaty introduces significant changes, particularly through its comprehensive framework for Environmental Impact Assessment (EIA), which is pivotal for island and developing nations. This paper employs qualitative research to analyse the role of Coastal States in the Indian Ocean region concerning the EIA process under the Treaty. For this purpose, it draws on primary sources such as treaty texts and official reports, as well as secondary sources including scholarly articles and expert analyses. The Indian Ocean, home to many developing nations and rich in marine biodiversity, holds considerable environmental, economic, and social value. Due to these factors, EIAs are critical for the region. This paper argues that the Treaty, viewed as a multilateral environmental agreement, offers Indian Ocean States a significant opportunity to participate in ocean governance, contribute to marine environmental conservation, and protect their self-interests. Through the EIA process, these States can update their domestic legislation and institutional structures, enhancing compliance with the United Nations Convention on the Law of the Sea (UNCLOS). However, challenges include potential marginalisation in decision-making and resource deficits. Despite the Treaty’s recent adoption, the paper concludes that the role of Indian Ocean States remains...
Keywords: Environmental Impact Assessment; High Seas Treaty 2023; Indian Ocean Region; Ocean Governance; Marine Resources Conservation; UNCLOS